Punctuation System Variability in Drama-Fairy Tale “Forest Song” by Lesia Ukrainka (Linguostylistic Studies, 2018)
The issue of the author's punctuation features as an element of the semantic system of a particular text has become a subject of scientific research only in the last decade, despite its importance for the semantic analysis of the text. This article examines the intonation patterns used in the dramatic works. The intonation patterns include speech melody, rhythm, phrasal (syntagmatic) stress and logical stress, intensity, voice tone, tempo and timbre. There are two main types of punctuation system: the author's individual writing style (author’s speech) and the character’s personal speech. The author’s speech punctuation subsystem is similar to the grammatical rules; the character’s speech punctuation subsystem functions as the intonation pattern in oral speech and is aimed at its logical division. The study has revealed and recorded the replacement of punctuation marks in the first-printed and modern editions of Lesya Ukrainka's drama-fairy tale "Forest song" and elucidated the nuclear and peripheral zones of the punctuation system, including the functional status of the dominant punctuation marks in the character’s personal speech and author’s remarks. The in-depth analysis of the drama shows that the largest number of lines belongs to Mavka; a comma is the most frequently used punctuation mark, it ensures the continuity of the rhythmic-melodic flow. Emotionally-expressive aspect is emphasized by the frequent use of ellipsis, exclamation and interogative marks. A similar punctuation picture is observed in Lukash's speech. The dynamics of punctuation is also typical for Rusalka (Mermaid), Mather of Lukash, Kylyna. A static punctuation picture is observed in the speech of Forest Elf, Will-o’-the-Wisp, and Water Goblin. A semicolon is often used by Lesya Ukrainka in remarks. The author's speech lacks emotionally-expressive coloring. It is characterized by the use of one-member sentences, two- member sentences, and asyndetic sentences. Among the remarks we can distinguish references to the place of action, clothes descriptions, interior remarks, landscape remarks, characters’ portraits, remarks commenting on the characters’ mood and mental state. The addressee and the specifics of the communicative situation also play a significant role in the formation of a punctuation pattern.
Keywords: punctuation mark; authors’ speech; character’s personal speech; functions of punctuation marks; dominant punctuation mark; dramatic work; remarks